MATH SOLVE

3 months ago

Q:
# 20. Solve –4(6x + 3) = –12(x + 10). A. x = 9 B. x = 2 C. x = –5 D. x = 5

Accepted Solution

A:

Answer:A. x = 9Step-by-step explanation:Note the equal sign, what you do to one side, you do to the other. First, distribute -4 to all 6x and 3, as well as -12 to x and 10.-4(6x + 3) = (-4 * 6x) + (-4 * 3) = -24x - 12-12(x + 10) = (-12 * x) + (-12 * 10) = -12x - 120-24x - 12 = -12x - 120Isolate the variable, x. Add 12 & 12x to both sides.-24x (+12x) - 12 (+12) = -12x (+12x) - 120 (+12)-24x + 12x = -120 + 12Simplify. Combine like terms.(-24x + 12x) = (-120 + 12)-12x = -108Isolate the variable, x. Divide -12 from both sides.(-12x)/-12 = (-108)/-12x = 9A. x = 9 is your answer.Check: Plug in 9 for x in the equation: –4(6x + 3) = –12(x + 10)-4(6(9) + 3) = -12(9 + 10)-4(54 + 3) = -12(19)-4(57) = -12(19)-228 = -228 (True)~